Rural residents’ Knowledge, Attitude, and Practice in relation to infection risk during the late stage of an epidemic: a cross-sectional study of COVID-19 - Zhuang, Manting; Zhai, Lixiang; Zhang, Hui; Chen, Qingsong; Xiong, Ran; Liu, Yonghui; Zhu, Fangyi (Frontiers in Public Health, 2024)
BackgroundIn the field of public health, the prevention and management of infectious diseases in rural regions have always been crucial. This study aims to analyze the factors influencing rural residents’ Knowledge, Attitude, and Practices and their correlation with infection risk during the late stage of an epidemic, with a focus on the COVID-19 case.MethodsA cross-sectional study was conducted in rural regions of China’s Guangdong province, using a multi-stage sampling technique to select rural residents for a validated questionnaire survey in February 2023. Descriptive statistical method was used to describe the infection status of rural residents and Chi-Square Test was used to explore the influencing factors of Knowledge, Attitude and Practice in this population. Multivariable binary logistic regression analysis was conducted to determine the presence of a statistically significant association between explanatory variables and outcome variables at corresponding 95% CI.ResultsA total of 3,125 rural residents were investigated, of whom 805 had never been infected with COVID-19. The survey participants had an average score of 5.84 ± 1.419 for COVID-19 knowledge. (The total score range is from 0 to 8. A score greater than 6.4 indicates good knowledge acquisition.) Regarding the attitude and practice sections, the average scores were 23.68 ± 3.169 and 23.45 ± 5.030, respectively. (The total score range of both these sections is from 0 to 32. A score greater than 25.6 represents positive attitudes and good practices.) The reduction of COVID-19 risk is significantly associated with an increase in Knowledge scores (p trend < 0.01). In stratified analyses, the Knowledge, Attitudes, and Practices scores of residents in each region have varying degrees of correlation with the risk of SARS-CoV-2 infection.ConclusionRural residents’ Knowledge, Attitudes, and Practices on COVID-19 prevention and control requires improvement. Efforts to promote their’ perceptions and habits regarding COVID-19 prevention and control are crucial in reducing the risk of infection.